Exploration of risk factors for the occurrence and recurrence of papillary thyroid carcinoma with Hashimoto's thyroiditis based on next-generation sequencing - Wanxue Zhang; Bin Liu (Diagnostic Pathology)
Abstract Objectives To investigate the risk factors for the occurrence and recurrence of Hashimoto's thyroiditis (HT) combined with papillary thyroid carcinoma (PTC) using Next-Generation Sequencing (NGS). Methods A total of 249 patients who underwent thyroid cancer surgery at the First Affiliated Hospital of Anhui Medical University from October 2020 to December 2020 were included in this study. They were divided into two groups: HT and non-HT (NHT) groups based on whether they were diagnosed with HT or not. Clinical data, NGS results, and 4-year follow-up recurrence were collected and analyzed using binary logistic regression and COX regression analysis to identify factors influencing the occurrence and recurrence of PTC with HT. Results Patients in the HT group had a higher percentage of low age, multifocality, high TgAb, and RET rearrangement compared to the NHT group. However, they had a lower rate of extrathyroidal extension (ETE), lymph node metastasis (LNM), and BRAF mutation (P < 0.05). Among patients with RET rearrangement in the HT group, there was a higher rate of LNM and recurrence (P < 0.05). Patients with BRAF mutation in the HT group were more likely to be male and have multifocal tumors (P < 0.05). Binary logistic regression analysis showed that multifocality, RET rearrangement, low age, and lymph node negativity were risk factors for HT combined with PTC. Univariate COX analysis revealed that multifocality, LNM, ETE, recurrence risk stratification, TSH, RET rearrangement, and the interaction between RET rearrangement and Hashimoto's effect were risk factors for recurrence after PTC. Multifactorial COX regression analysis showed that ETE and recurrence risk stratification were risk factors for recurrence after PTC surgery. Conclusions Multifocality, high TgAb, low age, and lymph node negativity can assist in the preoperative diagnosis of HT combined with PTC. BRAF mutations are less common in HT combined with PTC but do not significantly affect recurrence. Patients with RET rearrangement in addition to HT have a higher risk of recurrence, and special attention should be paid to intraoperative clearance in these patients.